Use of student self-assessment of exams to investigate student learning in organic chemistry classes - Karatjas, A.G. (ACS Symposium Series, 2014)
Post examination self-assessment surveys were utilized to explore student performance on examinations in organic chemistry courses. This study of student self-perception looked at the application of the Kruger-Dunning effect in organic chemistry courses. The results include a comparison of student performance to expectations and the amount of time spent preparing. Results for poorer performing students indicate a lack of connectivity between perception and actual results. © 2014 American Chemical Society.
Keywords: Organic Chemistry; Organic chemistry course; Self assessment; Student learning; Student performance; Student self assessments; Students; Time spent; dept.che